Tutoring program to develop social skills in students - Dávila-Soto, Rocío del Pilar (2020)
The present investigation had as objective: To determine the influence of the tutoring program in the development of social skills of the students of the Professional School of Initial Education. UNHEVAL 2018. For the analysis and interpretation of the results, the pre-experimental design with pre-test and post-test with a single application group was used and, through non-probability sampling, a working group consisting of 44 students from the IV cycle of the Professional School of Initial Education. A pre-test and post-test of 42 items were applied. Comparing the pretest and posttest of each dimension and the total consolidation of social skills, the following result was obtained: correlation index shows that the value of r = 0.40 and…. They are between 0.40 ≤ r <0.80 and their interpretation indicates that there is a significant influence between the Mentoring Program and the development of social skills of the students of the Professional School of Initial Education, UNHEVAL 2018.